Peningkatan Kompetensi Guru SLB dalam Pemanfaatan Teknologi Pembelajaran Digital di SLB YPAC Dewantara Aceh Utara - Hamdhana, Defry; Yusra, Muhammad; Maghfirah, Fitri; Mulyati, Sri; Kembaren, Emmia Tambarta (Lok Seva: Journal of Contemporary Community Service, 2025)
At SLB YPAC Dewantara, North Aceh, teachers' mastery of digital technology remains constrained in terms of the utilization of online applications and multimedia. The objective of this Community Service Program (PKM) is to enhance pedagogues' competencies through experiential learning, which is characterized by a participatory approach. The activity was conducted over the course of two days and involved 15 teachers. The materials covered the use of Zoom Meeting, Google Meet, Bitly, and the creation of simple animations using Canva and Powtoon. The evaluation results demonstrated a substantial increase in the utilization of digital tools, with the capacity to employ the fundamental functionalities of Zoom and Google Meet escalating from 27% to 87%, the application of Bitly rising from 13% to 80%, and the proficiency in generating animated media increasing from 7% to 73%. The challenges encountered by the participants included time constraints, variations in digital literacy, and internet infrastructure. This PKM fostered the establishment of an internal teacher learning community and underscored the significance of synergy among individual capacity, institutional support, and sustainable mentoring.